1983
DOI: 10.1093/clinchem/29.10.1825
|View full text |Cite
|
Sign up to set email alerts
|

Salivary urea nitrogen as an index to renal function: a test-strip method.

Abstract: To investigate the feasibility of using salivary urea nitrogen as an index of renal glomerular filtration rate, we developed and applied a new analytical system consisting of a urease-containing test strip and an automatic reflectance spectrometer. The concentrations of urea nitrogen so determined correlate well (r = 0.93) with concentrations in serum. These preliminary data suggest that our method can be used routinely as a simple and reliable means of detecting abnormalities of renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…The positive correlation between blood and salivary urea as well as creatinine observed in this study agrees with previous reports [ 14 , 23 , 24 ]. In addition, a study by Tomas et al [ 12 ] reported that concentrations of salivary urea were related to the severity of the kidney disease, and another study also showed that the concentration decreased with haemodialysis [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…The positive correlation between blood and salivary urea as well as creatinine observed in this study agrees with previous reports [ 14 , 23 , 24 ]. In addition, a study by Tomas et al [ 12 ] reported that concentrations of salivary urea were related to the severity of the kidney disease, and another study also showed that the concentration decreased with haemodialysis [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…[ 10 17 18 ] In fact, in one of the studies, salivary urea has been used as index to asses renal function. [ 19 ] Urea values observed in saliva were lower than in blood, may be considered as measure of efficiency of blood and saliva to purify themselves. Comparison between the two values showed significant statistical difference between the groups, but not within the groups as denoted by ANOVA and pairwise test.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Saliva urea nitrogen (SUN) was first described in the 1840s, 7 and several studies have since evaluated the diagnostic capability of SUN to detect renal impairment. 8 , 9 , 10 , 11 SUN parallels blood urea nitrogen (BUN) and urea reaches saliva by diffusive transport from the salivary glands. Alongside bicarbonate, it is responsible for the buffering capacity of saliva.…”
mentioning
confidence: 99%